On numerical modelling of stochastic systems - Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2025)
The paper considers a method to construct numerical models of non-markovian stochastic systems. The idea is to approximate a general distribution function of positive random value by mixture of exponential stages. The example is given.